Inflammation and innate immune system activation in neurodegeneration, Down syndrome, aging, and infection: Therapeutic target or partner?. (31st December 2021) - Potter, Huntington; Boyd, Timothy D.; Ahmed, Md. Mahiuddin; Kendall, Lon V.; Sillau, Stefan H; Coughlan, Christina M; Clarke, Penny; Stonedahl, Sarah; Chial, Heidi J
Abstract: Background: Characteristic features/biomarkers of innate immune system activation and inflammation are associated with neurodegenerative diseases (e.g., Alzheimer's disease [AD], Parkinson's disease [PD]), Down syndrome [DS], normal aging, and many infectious diseases. Evidence also suggests that peripheral inflammation interacts with and mirrors inflammation in the central nervous system (CNS) and can yield useful biomarkers of the disease or disorder and potentially of the efficacy of therapies. These findings have led to the additional conclusion that developing methods to dampen inflammation would be an effective therapeutic approach. However, recent findings indicate that innate immune system activation, including inflammation, may, instead, be beneficial. Method: We used the proinflammatory cytokine granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) to modulate the innate immune system and determine the effects on biomarker, clinical, and/or behavioral outcomes in mouse models of AD, DS, aging, and viral infection and in a clinical trial in AD. Result: Recent published and unpublished results from our laboratory and others show that treatment with GM‐CSF increases inflammatory biomarkers and also effectively reduces cognitive decline, brain pathology, and disease‐associated peripheral blood biomarkers in mouse models of AD, PD, DS, and normal aging. Interestingly, GM‐CSF treatment also reduces viral titer and mortality in mouse models of West Nile Virus and SARS‐CoV‐2 infection. Our retrospective study of patients with cognitive deficits due to chemotherapy‐induced CNS inflammation showed that recombinant human GM‐CSF (sargramostim) treatment was associated with improved cognition. A sargramostim clinical trial in PD also showed promising results. Finally, our recently‐completed clinical trial in AD showed that sargramostim treatment increased inflammatory cytokines and improved toward normal both a measure of cognition (MMSE) and blood biomarkers of amyloid (A) and Tau (T) deposition and neurodegeneration (N). Sargramostim clinical trials in COVID‐19 are underway. Conclusion: Together, these results indicate that targeted enhancement of the innate immune system and of inflammatory cytokines, specifically in response to GM‐CSF, can effectively treat many disorders that exhibit characteristic inflammation and innate immune system activation. Thus, the long‐held belief that inflammation and innate immune system activation only play a negative role in neurodegenerative diseases, DS, viral infections, and normal aging should be reassessed.